Multi-operative modular tool for cutting and mechanical hardening - Rosca, Dorin Mircea; Folea, Milena (IOP Conf. Series: Materials Science and Engineering, 2021)
It is well known the important role of the tools for mechanical processing in manufacturing within the present context of the rush for profitability and technical optimization for an environmentally friendly industrial production. Modularization of tools is a way to ensure their versatility being at the same time economically advantageous. In this paper, two milling cutters are adapted in order to be used also for surface hardening. The third tool described here is a newly designed modular tool that, according to needs, can be used to perform rough, finish milling or mechanical hardening.